Pharmaceutical development of etodolac transfersomal gel for topical drug delivery system in rheumatoid arthritis - Bachhav, Ashwini; Pingale, Prashant L; Upasani, Chandrashekhar D (Journal of Applied Pharmaceutical Research, 2024)
Background: Transferosomes provide delivery of the drug into systemic circulation via the skin as a topical delivery system. So, this study started with the objective of formulating Etodolac transfersomal gel to enhance its skin permeation. Methodology: A total of nine transferosomes (ET-1 to ET-9) containing lecithin, different grades of span and tween, were successfully prepared using a rotary film evaporator. Results and Discussion: After primary evaluation, results were as particle sizes ranged from 222 to 421 nm, zeta potential shows results from –18.50 to –62.53 mV with PDI values 0.254 to 0.303, and the entrapment efficiency (EE%) of Etodolac in the transferosomes ranged from 54.15% to 80.25%. Additionally, the transfersomes formulations were included in carbopol 940 gels (ETC-1 to ETC-9 and EC-0 without transferosomes) and assessed for various characteristics like color, pH, homogeneity, spreadability, viscosity, and in vitro drug release study. Optimized formulation (ET4 and ETC4) underwent further analysis using SEM, TEM, DSC, FTIR, XRD, ex vivo skin permeation, skin irritation and in vivo studies. The in vivo results were compared. % edema inhibition maximum was observed with optimized transfersomal gel formulation (ETC4) as compared to the marketed formulation and plain Carbopol gel when the study was completed after 8 hrs. Conclusion: After this research, it is suggested that Etodolac Transfersomal gel (ETC4) can be considered as an alternate drug carriers system for topical delivery and it could be used to treat Rheumatoid Arthritis